2013
DOI: 10.1128/mcb.00678-12
|View full text |Cite
|
Sign up to set email alerts
|

Large FK506-Binding Proteins Shape the Pharmacology of Rapamycin

Abstract: The immunosuppressant and anticancer drug rapamycin works by inducing inhibitory protein complexes with the kinase mTOR, an important regulator of growth and proliferation. The obligatory accessory partner of rapamycin is believed to be FK506-binding protein 12 (FKBP12). Here we show that rapamycin complexes of larger FKBP family members can tightly bind to mTOR and potently inhibit its kinase activity. Cocrystal structures with FKBP51 and FKBP52 reveal the modified molecular binding mode of these alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 58 publications
0
101
0
3
Order By: Relevance
“…Intrigued by our initial finding that rapamycin can tightly bind to most members of the FKBP family, 14 we asked whether larger FKBP homologs contribute to the pharmacology of rapamycin in mammals. 15 We found that all tested human FKBPs (FKBP12, 12.6, 13, 25, 51, 52) could potently form rapamycin-induced ternary complexes with the FRB domain of mTOR and inhibit mTOR kinase activity. Genetically and pharmacologically we could show that FKBP12 is dispensable in mammalian cells for the action of rapamycin, and that it can be functionally replaced by larger FKBPs.…”
Section: Fkbps the Enablers Of Rapamycinmentioning
confidence: 89%
See 2 more Smart Citations
“…Intrigued by our initial finding that rapamycin can tightly bind to most members of the FKBP family, 14 we asked whether larger FKBP homologs contribute to the pharmacology of rapamycin in mammals. 15 We found that all tested human FKBPs (FKBP12, 12.6, 13, 25, 51, 52) could potently form rapamycin-induced ternary complexes with the FRB domain of mTOR and inhibit mTOR kinase activity. Genetically and pharmacologically we could show that FKBP12 is dispensable in mammalian cells for the action of rapamycin, and that it can be functionally replaced by larger FKBPs.…”
Section: Fkbps the Enablers Of Rapamycinmentioning
confidence: 89%
“…First, the C terminus of the FK506-binding domain of FKBPs points to the hinge region of mTOR, and therefore the additional C-terminal domains present in larger FKBPs (FKBP-like domains and tetratricopeptide repeat domains) can be expected to be located in this region in ternary FKBP-rapamycin-mTOR complexes. It should be noted that the truncated mTOR kinase (mTOR ΔN ) used to determine the inhibitory potency of different FKBPs 15 was almost identical to the protein construct used for the crystallization of the FAT-FRB-kinase domain of mTOR. 5 Since the larger FKBPs inhibited mTOR ΔN in the presence of rapamycin almost as efficiently as FKBP12, 15 it seems that: (1) the additional C-terminal FKBP domains do not engage in additional inhibitory interactions; and (2) the intramolecular domain arrangements of the larger FKBPs are flexible enough to avoid clashes with mTOR.…”
Section: The Fkbp-rapamycinmtor Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Anyhow, in FKBP51/52, a glycine (Gly84) replaces the Gln53 of FKBP12, similar to the Gly169 in FKBP25. When comparing the structures of FKBP51 in complex with FK506 13 (PDB ID 3O5R) and rapamycin 14 (PDB ID 4DRI), we observed that the hydrogen bond interaction by Gly84 with rapamycin is lost in FK506, similar to FKBP25. But the Glu54 in FKBP12, which is substituted by a Gln85/Glu85 in FKBP51/52, does not make hydrogen bonds with rapamycin unlike the equivalent Lys170 in FKBP25, revealing the importance of Lys170, which is highly unique to FKBP25.…”
Section: Interactions Of Fk506 With Hfkbd25mentioning
confidence: 99%
“…FKBP51, which is coded by the FKBP5 gene, is a negative regulator of glucocorticoid action and reduces glucocorticoid receptor-binding affinity [10]. When corticosteroid binds to its receptor, FKBP51 is replaced by FKBP52 [11]. As a result, overexpression of FKBP51 decreases receptor regulation by FKBP52 [9].…”
Section: Introductionmentioning
confidence: 99%